REVIEW OF THE DIVERSE ASSESSMENT METHODS OF THE INSOMNIA DISORDER - Ruiz, Cristina (Anales de Psicología / Annals of Psychology, 2007)
The current study carries out a review of the most widely used assessment methods of the insomnia disorder: subjective measurements (clinical interviews, scales and questionnaires on sleep, self-assessments), psychological screening and objective measurements (psychophysiological measurements). The article points out the discrepancies between these methodologies and emphasizes the importance of a detailed and comprehensive assessment. There are numerous methods of subjective assessment which attempt to cover the different parameters involved in the sleep process and the consequences of lack of sleep. However, there is not a single tool that covers the diverse sleep parameters. Furthermore, as the majority of assessment systems are aimed at a healthy adult popula-tion it would seem relevant to design a tool specifically directed at a population of high risk insomnia sufferers, such as geriatric and hospital-ized population.